2013
DOI: 10.1097/ico.0b013e318243e474
|View full text |Cite
|
Sign up to set email alerts
|

Confocal Microscopy of Corneal Crystals in a Patient With Hereditary Tyrosinemia Type I, Treated With NTBC

Abstract: This is the first in vivo demonstration by confocal microscopy of corneal crystals present in a patient with proven type I tyrosinemia, under NTBC treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 9 publications
(8 reference statements)
2
13
1
Order By: Relevance
“…This may be consistent with the diurnal variation in the circulating tyrosine, known to be higher late in the day and lowest first thing in the morning (Fernstrom et al 1979). A similar diurnal variation in ocular pain in the evenings has been reported previously (Schauwvlieghe et al 2012). The symptoms on alternate days could be explained by the nitisinone dosing on alternate days; he could clarify whether his symptoms were on the day of administering nitisinone or the following.…”
Section: Discussionsupporting
confidence: 88%
“…This may be consistent with the diurnal variation in the circulating tyrosine, known to be higher late in the day and lowest first thing in the morning (Fernstrom et al 1979). A similar diurnal variation in ocular pain in the evenings has been reported previously (Schauwvlieghe et al 2012). The symptoms on alternate days could be explained by the nitisinone dosing on alternate days; he could clarify whether his symptoms were on the day of administering nitisinone or the following.…”
Section: Discussionsupporting
confidence: 88%
“…In that report, Schauwvlieghe et al confirmed the presence of slender birefringent spiky crystals in the superficial corneal epithelium with confocal microscopy. 11 Unlike the patient reported previously by Ahmad et al, despite stopping the NTBC treatment and the lack of the corneal symptoms, their case still experienced a relatively high tyrosine level of 650 mmol/L. Despite the decrease in tyrosine levels and the complete resolution of the corneal findings with dietary restrictions, our case also still manifested elevated tyrosine levels.…”
Section: Discussioncontrasting
confidence: 79%
“…Ocular involvement is not frequent in HT1 patients, but in those rare cases corneal keratitis is the main manifestation (31, 32). This has been attributed to inflammation produced by local tyrosine deposition in the form of crystals caused by low compliance with a low protein diet and the secondary effect of using NTBC on tyrosine accumulation.…”
Section: Resultsmentioning
confidence: 99%
“…Ocular involvement is rare in patients with HT1 but frequent in patients with tyrosinemia type II (46), which is produced by mutations in tyrosine transaminase, the enzyme undertaking the first step of tyrosine catabolism. As with tyrosinemia type II, corneal keratitis in HT1 patients and possibly FAH knock-out rabbits as well is caused by enhanced local accumulation of tyrosine, which is boosted by NTBC (31, 32). The frequency with which ocular manifestations happen in FAH −/− rabbits potentially makes them a useful model for studying how to prevent and treat this potential complication in HT1 patients.…”
Section: Discussionmentioning
confidence: 99%